Generalized Subcutaneus Emphysema in Shih Tzu Mixed Breed Dog: A Case Report - Milda Lailia; Putu Ayu Sisyawati Sisyawati; I Gusti Made Krisna Erawan (Journal of Veterinary and Animal Sciences, 2023)
Abstract. Generalized subcutaneous emphysema is a rare occurrence in large and small animals. The author reports a case of a male Shih Tzu mixed breed dog, 5 years old, with a body weight of 7.74 kg, that presented with gas accumulation over almost the entire body for two days prior to the examination. The previous week, the owner reported that the dog was fighting with other dogs around the house. Physical examination of the dog revealed crepitation to palpation with gentle pressure on the head and extremities. Inspection revealed a massive tick infestation, but there were no injuries. Radiographs showed subcutaneous air accumulation throughout the body. Hematology showed elevated level of total leukocytes and lymphocytes, consistent with infection. The dog was diagnosed with generalized subcutaneous emphysema due to trauma from fighting with other dogs, with a favorable prognosis. Treatment options for the dog included needle aspiration, bandaging, and antibiotic and anti-inflammatory therapy. Antibiotics administered included cefadroxil monohydrate (Cefadroxil Hexpharm®, PT Hexpharm Jaya Laboratories, Indonesia) at doses of 10-25 mg/kg BW, given orally as 6 mL twice daily for 7 days. Anti-inflammatory medication in the form of carprofen (Rimadyl®, Zoetis Inc.) was administered at a dose of 4.4 mg/kg BW, given as one tablet orally per day for 7 days. Evaluation was conducted weekly to monitor the animal's progress. After two weeks of treatment, the dog was declared cured when no subcutaneous gas was observed.